Anterior temporal artery to posterior cerebral artery bypass for revascularization of the posterior circulation: An anatomical study. (January 2018) - Yağmurlu, Kaan; Kalani, M. Yashar S.; Chaddad-Neto, Feres; Cevik, Orhun Mete; Bozkurt, Baran; Belykh, Evgenii; Doria-Netto, Hugo Leonardo; Grande, Andrew W.; Preul, Mark C.; Spetzler, Robert F.
Highlights: An ATA-to-PCA anastomosis is feasible to revascularize the posterior circulation. Harvesting the ATA poses a significantly lower risk of ischemia due to parent artery occlusion during anastomosis. The ATA can be an alternative to extracranial bypass donor segments for revascularization of complex aneurysms. Abstract: We describe a novel intracranial-to-intracranial bypass technique between the anterior temporal artery and the posterior cerebral artery for revascularization of the posterior circulation. Four formalin-fixed human heads were examined to demonstrate the detailed anatomy of the middle cerebral artery and the posterior cerebral artery, and to illustrate the step-by-step bypass procedure. The anterior temporal artery, a branch of the middle cerebral artery, can be anastomosed to the P2 segment of the posterior cerebral artery as an alternative to extracranial bypass donor segments for treatment of complex aneurysms requiring revascularization. The anastomosis of the anterior temporal artery as a pedicled donor to the posterior cerebral artery provides a shorter graft, due to its close anatomical position to the posterior cerebral artery, for posterior circulation revascularization.